Blockchain Technology and Inclusive Financial Systems in the Global South - Thilagavathi K.; C. Jayamala; Thankamani K.; P. Shunmukapriya (International Journal of Mobile Computing Technology, 2024)
This paper explores how blockchain technology can promote financial inclusivity by providing decentralized, transparent, and secure financial services, particularly in the Global South, where conventional banking systems are frequently insufficient. Through a blend of literature review and empirical analysis, we assess blockchain's role in expanding financial access, using case studies from several developing nations. Our results reveal a promising potential for blockchain to improve financial inclusion, although obstacles such as regulatory and technological challenges persist. By harnessing blockchain, unbanked and underbanked communities in the Global South may access financial services that are more efficient, affordable, and dependable. This study explores specific blockchain applications, including digital identity verification, smart contracts, and decentralized finance (DeFi) platforms, which can address limitations within traditional banking systems. Furthermore, it examines the socioeconomic advantages blockchain adoption could offer, such as poverty reduction, increased economic activity, and enhanced financial literacy. The paper also underscores challenges to widespread blockchain adoption, such as the need for regulatory clarity, sufficient technological infrastructure, and greater public awareness. The study offers guidance for policymakers, financial institutions, and technology developers on creating an environment conducive to blockchain integration. It concludes that, although blockchain alone cannot resolve all issues, it presents a valuable opportunity to enhance financial inclusion and economic empowerment in the Global South.
Keywords: Blockchain technology; Financial Inclusion; Global South; decentralized finance; developing countries; digital currency; economic development; financial innovation; financial systems; fintech